Ministry of Trade & Industry Decree No. 371 of the Year 2018 On Amending the Local Manufacture percentage in the Automotive Industry, and the Method of calculating such percentage = وزارة التجارة والصناعة قرار رقم 371 لسنة 2018 فى شأن تعديل نسبة التصنيع المحلى فى صناعة السيارات وطرق احتسابها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic